2016
DOI: 10.1108/dpm-08-2015-0196
|View full text |Cite
|
Sign up to set email alerts
|

Vested interest: developing scales for assessing flooding preparedness

Abstract: Purpose -The purpose of this paper is to report research testing scales developed from a combination of vested interest (VI) theory and the extended parallel process model of fear appeals. The scales were created to measure variables specified by an expanded model of VI: certainty, salience, immediacy, self-efficacy, response-efficacy, and susceptibility. Design/methodology/approach -A survey was designed with subscales for each element and combined with additional disaster and risk perception variables. Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…Athletes were asked to respond to scales measuring vestedness in attitudes related to their risk perception and decision-making related to suffering SHIs (see S3 Table). Vested Interest Scales were modified from natural hazard research to fit the present context; construction and validation of these scales, as well as the risk perception scale, is reported in existing publications [20,31,58]. We modified the Vested Interest Scales for the SHI context by substituting appropriate nouns and phrases into the items.…”
Section: Methodsmentioning
confidence: 99%
“…Athletes were asked to respond to scales measuring vestedness in attitudes related to their risk perception and decision-making related to suffering SHIs (see S3 Table). Vested Interest Scales were modified from natural hazard research to fit the present context; construction and validation of these scales, as well as the risk perception scale, is reported in existing publications [20,31,58]. We modified the Vested Interest Scales for the SHI context by substituting appropriate nouns and phrases into the items.…”
Section: Methodsmentioning
confidence: 99%
“…Flooding remains the costliest and deadliest natural hazard, accounting for 40% of all natural disasters and half of all disaster-related deaths [1], [2]. Historical records have shown that coastal megacities situated in developing nations suffer the most from flood disasters, mainly due to huge population exposure, and more critically, the lack of actionable data and poor situational awareness that undermine the efforts of flood control operators, first responders and emergency services [3].…”
Section: Introductionmentioning
confidence: 99%
“…Similar iterations of these subscales have been used in related risk perception research; results from related studies show that the scales are robust to modification across contexts. Details concerning development, reliability, validation, and context-based modification of these scales are reported elsewhere (Adame & Miller, 2016; Miller, Adame, & Moore, 2013), as is their use in concussion-related research (Adame & Corman, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…As a theory of the attitude–behavior relationship, VI is valuable both as an audience analysis tool and as a frame for designing effective persuasive health communication campaigns (Adame & Miller, 2015). Communicative and environmental interactions can influence overall vestedness (Adame & Miller, 2016). In risk communication contexts, research has demonstrated that perceived vestedness can be manipulated through VI-based campaigns, and the VI-based messages are effective in motivating self-protective behavior (Adame & Miller, 2015; De Dominicis et al, 2014).…”
Section: Theorymentioning
confidence: 99%